Aplicación de CLASlite como herramienta para monitorear deforestación y degradación de los bosques en la Región Norte-Atlántica de Costa Rica - Malavasi-Pastrana, Andreina (Instituto Tecnológico de Costa Rica, 2015)
Deforestation and forest degradation are processes that have led forest ecosystems to a temporary, sometimes permanent, deterioration of the species’ density and composition, which affects their productive capacity. Since both processes are difficult to monitor, the use of CLASlite program has been proposed. Landsat images of the years 2014 and 2015 were first processed with CLASLite, then a validation of the results was completed in the field. Deforested, degradated and control sites in the different farms under contract with FUNDECOR were visited. Circular plots of 15 m radius where established in these sample sites, and basal area, above ground biomass, and brightness percentage were calculated. The field test showed significant differences between the tested locations. CLASLite degraded sites have lower basal area and above ground biomass, and higher brightness percentage values than the control sites. With respect to the sites that CLASlite identified as deforested, the field validation shows a classification error of 66.7%. Therefore, the field test indicates that the use of CLASlite is an accurate method for monitoring forest degradation; nevertheless, it is not recommended for monitoring deforestation.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2015.
Keywords: CLASlite; Sensores remotos; Landsat; Biomasa; Luminosidad